Jamaica - Early Childhood Development Project : Project Performance Assessment Report - World Bank (Washington, DC, 2022)
Ratings for the Early Childhood Development Project are as follows: Outcome was moderately unsatisfactory, Bank performance was moderately unsatisfactory, and Quality of monitoring and evaluation was modest. This assessment offers the following lessons: (1) Collaboration, strong national ownership of the NSP, and financial support are requisite conditions but do not ensure performance and outcomes because the World Bank must also provide rigor and candor in its dialogue and advice. (ii) Country teams need to share and archive lessons and implementation knowledge, including Global Practice knowledge, across projects. (iii) The institutional arrangements for cross-sectoral or cross-ministerial action and coordination are less likely to succeed when authority is centered in one of the involved ministers or ministries. (iv) Intersectoral coordination may more likely be sustained with “light mechanisms” and financial resources that empower ministries and national agencies to focus on achieving a convergence of common policies, actions, and results.